OCORRÊNCIA E DETERMINAÇÃO DE TRICLOSAN EM ÁGUAS DE ABASTECIMENTO NA BACIA DO RIO PITANGUI - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
Emerging micropollutants are characterized as potential risk factors for the environment and for human health. Among these micropollutants is Triclosan (TCS), with antimicrobial action that has been widely used mainly in personal care products which in the environment can affect the biota and produce bacterial resistance. This study aimed to evaluate the presence of TCS in surface waters and effluent from the Sewage Treatment Plant (STP). Surface water samples were collected (10 samples) in the urban area of the city of Ponta Grossa in Arroio Pilão de Pedra (point 1), the Rio Verde upstream (point 2) and downstream (point 3) of the ETE and effluent samples collected within the ETE Rio Verde before (point 4) and after anaerobic treatment (point 5), thus evaluating the effluent itself and the presence of TCS. Physical and chemical evaluations were also conducted on points 1, 2 and 3 in order to verify the quality of the aquatic environment. The techniques used for the physical-chemical evaluations were based on Molecular Spectroscopy UV absorption, which are all carried out in triplicate. As for the determination of TCS, a high performance chromatography liquid was employed (HPLC) preceded by pre-concentration in the solid state with the technique being implemented after validation. The chromatographic analyzes were performed employing a chromatograph Allcrom YL9100 with C-18 (250 mm x 4.6 mm x 5 m), mobile phase acetonitrilal / water (65:35) with isocratic elution and UV-Vis detector. The solvents used are all HPLC grade and ultrapure Milli-Q water . The chromatographic analyzes were performed under a flow (output) of 1mL/min, injection volume 400 μL, average pressure of 2360 psi and a temperature of 30 º C. The pre-concentration of the samples was performed using the technique of solid phase extraction (SPE) using cartridges C18/18 Applied Separations. The physical-chemical evaluation of the samples collected in the Green River showed a decline in the quality of the water after disposal of treated effluent. High biochemical oxygen demand (BOD) and high chemical oxygen demand (COD), high concentrations of total organic carbon (TOC), surfactants (SFT) and total phosphorus (TPHO), as well as reduced levels of dissolved oxygen (DO) were observed in the Rio Verde downstream of ETE. The Arroio Pilão de Pedra showed similar characteristics to the Rio Verde after disposal of treated effluent. TCS was detected in two of the selected points for the chromatographic analysis (points 3 and 4) at concentrations averaging 33, 23ug L-1 points. The results demonstrate a relationship between waters impacted by raw sewage or the effluent of ETE inflow, and the presence of TCS.
Keywords: Triclosan; cromatografia líquida de alta eficiência; águas superficiais; efluente; Triclosan; high performance liquid chromatography; surface water; effluent; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA